Investigating the pseudo – Capacitive properties of interlayer engineered VOPO4 by organic molecule intercalation. Issue 18 (15th September 2022) - Amedzo-Adore, Mawuse; Han, Jeong In
Abstract: The varying oxidation states of vanadium has given vanadium phosphate-based compounds a very rich chemistry, that has resulted in increasing interest in them for varying applications such as energy storage systems, including supercapacitors. Among them is vanadyl phosphates that exist in several polymorphs and have seen lots of research on their applications in alkali metal rechargeable batteries. Layered VOPO4 is of much interest due to its ability to undergo intercalation reaction. In this work, an organic molecule (triethylene glycol) was successfully intercalated into the layers of VOPO4 in a two-step solvothermal reaction. This approach resulted in exfoliation of VOPO4 layers leading to enlarged interlayer spacing, as well as enhancing the conductivity by reducing the band gap of the material. The intercalated material (TrEG-VOP) demonstrated an enhanced supercapacitor properties with capacitance 473 Fg -1 and capacitance retention of 80% against capacitance 400 Fg -1 and capacitance retention of 55% for the pristine (VOP)